Information base of technologicaly oriented programming systems for automatic programming of NC machine tools - Gatalo, Ratko; Hodolič, Janko; Zeljković, Milan (Journal of Production Engineering, 2023)
The main objective of this paper is an integral programming system for the automatic design of technological processes and programming NC flexible manufacturing systems (FMS) for rotational parts. It is developed as an extension of the SAPOR-S programming system for NC lathes. The technological information base of the SAPOR-S system is detailed concerning its concept, information sheets, file organization, and programming support. The conception of the information base for SAPOR-FTS architecture is also briefly presented